Herbicide programs, cropping sequences, and tillage-types: a systems approach for managing Amaranthus palmeri in dicamba-resistant cotton - Vulchi, Rohith; Nolte, Scott; McGinty, Joshua; McKnight, Benjamin (Frontiers in Agronomy, 2023)
Herbicide-resistant Amaranthus palmeri poses a significant threat to cotton production in the United States. Tillage, cover crops, crop rotations and dicamba-based herbicide programs can individually provide effective control of A. palmeri but there is lack of research evaluating the above tactics in a system for its long-term management. Field trials were conducted near College Station and Thrall, TX (2019-2021) to evaluate the efficacy of dicamba-based herbicide programs under multiple cropping sequences and tillage types in a systems approach for A. palmeri control in dicamba-resistant cotton. The experimental design used was a split-split plot design. The main plots were no-till cover cropping, strip tillage, and conventional tillage. The subplots were cotton:cotton:cotton (CCC) and cotton:sorghum:cotton (CSC) sequences for three years within each tillage type; and sub-subplots were a weedy check (WC), weed-free check (WF), low input program without residual herbicides (LI), and a high input program with residual herbicides (HI). Using HI under CSC sequence was the only system that provided >90% control of A. palmeri for three years across all tillage types and locations. By 2021, A. palmeri densities in CSC sequence at College Station (4156 plants ha-1) and Thrall (4006 plants ha-1) are significantly low compared to CCC sequence (31364, 9867 plants ha-1 respectively) when averaged across other factors. Similarly, A. palmeri densities in HI at College Station (9867 plants ha-1) and Thrall (1016 plants ha-1) are significantly low compared to LI (25653, 13365 plants ha-1 respectively) when averaged across other factors. We also observed CSC sequence reduced A. palmeri seedbank by at least 40% compared to CCC sequence at both College Station and Thrall when averaged across other factors. Over three years, we didn’t observe significant differences between LI and HI for cotton yields at College Station (1715-3636 kg ha-1) and Thrall (1569-1989 kg ha-1). However, rotating cotton with sorghum during 2020 improved cotton yields by 39% under no-till cover cropping in 2021 at Thrall. These results indicate using dicamba based herbicide programs with residual herbicides and implementing crop rotations can effectively manage A. palmeri in-terms of seasonal control, densities and seedbank buildup across tillage types and environments.